NURSING WORK: NURSES AND USERS’ POINT OF VIEW - Barrientos, María Clara Pesutic; Pires, Denise Elvira Pires de; Machado, Rosani Ramos (My University, 2020)
ABSTRACT Objective: to understand the perception of users and nurses about nursing work. Method: a descriptive exploratory qualitative research in a clinic inpatient unit of a public hospital and in a Family Health Center, in the city of Punta Arenas, Chile. For data collection, we worked with a semi-structured interview, and analysis of the information was carried out guided by thematic content analysis. Thirty-five users and sixteen nurses participated; data collection took place between September and December 2018. Results: the results were organized according to the perception of nurses and users into four thematic categories Nursing as a profession of human care; Nursing and its role in administration/management; Nursing as a profession with educational role; Nursing as a health profession. In the case of users, nursing qualification as heavy and arduous work also emerged. Conclusion: nurses and users consider nursing as a health profession that deals with human care, which involves not only healing, but also dimensions of health education and management of material and human resources, which is based on science and requires academic training for proper development at different levels of care.
Keywords: nursing; nurse-patient relations; nursing care; nurse’s role; social perception; humanization of assistance